The Legal Responsibility of Insurance Companies towards Customers for Mistakes by Commercial Health Insurance Agents in Indonesia - Angdiarto, Ricardo Stanislaus; Huda, Mokhamad Khoirul (Universitas Katolik Soegijapranata Semarang, 2024)
The relationship between the health insurance company and the customer is a coverage relationship which is proven by the existence of an insurance policy. KThe authority of an insurance agent to market an insurance product comes from an Agency Agreement.The insurance company's legal responsibility related to insurance agent errors can take the form of criminal, civil and administrative responsibility. The research aims 1) to explain the legal relationship of the parties in the health insurance agreement and 2) to explain the legal responsibility of the insurance company related to the insurance agent's error for health. The type of research used in writing this research is normative juridical research, namely research that examines the internal aspects of positive law. There are several types of approaches in legal research that were used in the preparation of this paper, namely 1) Statute approach, namely the approach used to study and analyze all laws and regulations relating to the legal issue being handled.[1]; 2) Conceptual approach (conceptual approach). The relationship between the agent and the helath insurance company is a contractual relationship as evidenced by an agency agreement for health. Agents act for and on behalf of insurance companies, where agents market and sell insurance products. The relationship between the insurance company and the customer is a coverage relationship which is proven by the existence of an insurance policy. The authority of an insurance agent to market an insurance product comes from an Agency Agreement. The conclusion of research showed that the legal relationship between the parties is interrelated and there is a policy agreement.